Multi-textualism, ’Treaty Hegemony’ and the Waitangi Tribunal: Making Sense of 19th Century Crown-Māori Negotiations in Te Urewera - Blumhardt, Hannah (Victoria University of Wellington Law Review, 2012)
Between 1894 and 1896 the Crown conducted negotiations with Tūhoe which culminated in the 1895 Urewera Agreement and the Urewera District Native Reserve Act 1896. This article considers the constitutional implications of these negotiations and the resulting agreement and legislation. Adopting a ’multi-textual’ conception of New Zealand legal history, and paying heed to the fact that Tūhoe did not sign the Treaty of Waitangi, the article argues that the Crown-Tūhoe relationship should be grounded predominantly in the 1895–1896 Agreement rather than the Treaty of Waitangi. In making this argument the article critiques the Waitangi Tribunal’s approach to these particular points in the first two pre-publications of its Te Urewera Report. The article argues that in finding that the Crown-Tūhoe negotiations and agreement signalled the beginning of a relationship based upon the Treaty of Waitangi, the Waitangi Tribunal erred in its approach.